An Acetylcholinesterase Biosensor Based on Graphene/Polyaniline Composite Film for Detection of Pesticides. Issue 1 (8th January 2016) - Li, Yanping; Zhang, Yuyu; Han, Gaoyi; Xiao, Yaoming; Li, Miaoyu; Zhou, Wen
Abstract: This work reports a sensitive amperometric biosensor for organophosphate pesticides (OPs) fabricated through modifying glassy carbon electrode with acetylcholinesterase (AChE) immobilized on graphene/polyaniline (G/PANI) composite film. The obtained G/PANI composite films show large specific area, high conductivity, good biocompatibility, and fast redox properties and have perfect layered and encapsulated structures. The as‐prepared biosensor shows high affinity to acetylthiocholine (ATCl) with a Michaelis‐Menten constant value of 0.20 mmol/L. Furthermore, based on the inhibition of the enzymatic activity (immobilized AChE) caused by the model compound of carbaryl (one kind of pesticides), it is found that the inhibition activity of carbaryl is proportional to its concentration ranging from 38 to 194 ng·mL −1 . The developed biosensor shows a detection limit of 20 ng·mL −1 ( S / N =3) for OPs detection and exhibits good performance such as good reproducibility and acceptable stability, which makes it possible to provide a new and promising tool for the analysis of enzyme inhibitors. Abstract : A novel interface G/PANI composite film was constructed during the electrodeposition. The resulting G/PANI‐based enzyme biosensor exhibited excellent sensitivity, good stability, fast electrochemical response and good reproducibility.